(untitled) (NAU Journal of Technology and Vocational Education, 2025)
This study investigated perception and readiness of Nigerian business educators towards adoption of AI-Based learning tools. The population of the study included business educators from various educational institutions in Nigeria and a sample size of 250 participants was used. The study utilized two research questions to explore the perceptions and readiness of Nigerian business educators towards AI-based learning tools. The researchers employed a survey instrument to collect data, which was tested for reliability using Cronbach’s alpha method. The results showed a high level of readiness and positive attitudes among the Nigerian business educators towards the adoption of AI-based tools, such as personalized learning platforms, automated grading systems, and virtual tutors. The findings highlighted the business educators’ recognition of the potential benefits of AI in addressing educational challenges, as well as their confidence in integrating AI-driven automated grading systems into their teaching practices. However, the study also identified perceived barriers, including inadequate infrastructure, insufficient training, and ethical concerns, which need to be addressed to ensure successful AI integration. One of the key recommendations from the study is to implement comprehensive training and professional development programs for Nigerian business educators, focusing on the practical implementation of AI-based learning tools. This will enhance their confidence, competence and ability to effectively integrate these technologies into their teaching practices.